Pemberdayaan Masyarakat Desa Hutan Melalui Pendampingan Digitalisasi Produk UMKM - Roisatul Ainiyah; Mukhammad Ali Saputra; Evi Ratna Widya Safitri (Jurnal Pengabdian dan Peningkatan Mutu Masyarakat (Janayu), 2026)
Purpose – This activity aims to enhance the partners’ capacity in managing, marketing, and developing Non-Timber Forest Products (NTFPs) through a digitalization approach. Design/methodology/approach – The method employed in this program was Participatory Action Research (PAR), with activities consisting of product photography training, assistance in creating digital content, and guidance in establishing e-commerce accounts. The implementing team comprised lecturers and students from Yudharta University Pasuruan. The partners involved in this activity were micro, small, and medium enterprises (MSMEs) and karang taruna in Ledug Village, Prigen Sub-district, Pasuruan Regency.. Findings – This community engagement activity successfully improved the partners’ skills in product photography, digital content creation, and the utilization of social media and online marketplaces, with an average evaluation score of 3.31 (categorized as good). However, challenges related to equipment, internet connectivity, and digital literacy were still encountered, indicating the need for further assistance. Originality/value – The originality of this activity lies in the product digitalization mentoring model, which holistically integrates product photography training, digital content development, and the utilization of e-commerce to enhance digital literacy, marketing skills, and partner independence in expanding the market access of local products.